UNA CRISIS Y UNA SALIDA DIFERENTES? EL CASO DE LA COMUNIDAD AUTÓNOMA DEL PAÍS VASCO - Aranguren, María José; Navarro, Mikel; Peña, Iñaki (Papeles de economía española, 2013)
We study the current economic recession of the Basque Country. The region shows a distinctive economic condition prior to the recession and evolves differently compared to most regions of Spain during the crisis period. Economic and innovation indicators of the Basque Country are compared to those of other referent European regions to illustrate the competitive position of the Basque region in Europe. Additionally, the design and implementation of recent public policies in the Basque Country are explained.